2020
DOI: 10.1186/s13071-020-04242-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and utility of mitochondrial ribosomal genes for molecular systematics of parasitic nematodes

Abstract: Background: Molecular advances have accelerated our understanding of nematode systematics and taxonomy. However, comparative analyzes between various genetic markers have led to discrepancies in nematode phylogenies. This study aimed to evaluate the suitability of using mitochondrial 12S and 16S ribosomal RNA genes for nematode molecular systematics. Methods: To study the suitability of mitochondrial 12S and 16S ribosomal RNA genes as genetic markers for nematode molecular systematics, we compared them with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…For nematodes, the mitochondrial 12S and 16S rRNA genes exhibited the best resolution of the genetic markers (apart from NAD 1 for nematodes), with four out of six orders as monophyletic. The mitochondrial rRNA genes are more conserved than the mitochondrial protein-coding genes, and this slightly more conserved nature has led to the mitochondrial rRNA genes being used for higher-level classification of organisms [ 57 59 ]. In helminths, the 16S rRNA gene and the nuclear rRNA genes have been used in conjunction to provide increased resolution for cestode phylogenies [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For nematodes, the mitochondrial 12S and 16S rRNA genes exhibited the best resolution of the genetic markers (apart from NAD 1 for nematodes), with four out of six orders as monophyletic. The mitochondrial rRNA genes are more conserved than the mitochondrial protein-coding genes, and this slightly more conserved nature has led to the mitochondrial rRNA genes being used for higher-level classification of organisms [ 57 59 ]. In helminths, the 16S rRNA gene and the nuclear rRNA genes have been used in conjunction to provide increased resolution for cestode phylogenies [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In helminths, the 16S rRNA gene and the nuclear rRNA genes have been used in conjunction to provide increased resolution for cestode phylogenies [ 60 , 61 ]. Chan et al also reported that the mitochondrial rRNA genes provide good resolution and can be used for molecular systematics in nematodes [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the short amplicon length increases the chances of successful PCR amplification, rendering them useful to amplify archived specimens, especially for DNA barcoding studies. Similarly, primers targeting parasitic nematode species of medical importance were designed and evaluated for molecular systematics and identification, showing the possibility of utilizing the mitochondrial rRNA genes for DNA barcoding of nematodes [ 27 ]. Although the current DNA barcode of choice is the mitochondrial COI gene, the potential of the mitochondrial rRNA genes for DNA barcoding of trematodes cannot be undermined.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial 12S and 16S rRNA genes have been utilized for molecular studies of helminths, albeit not widely. Chan et al revealed the potential of the mitochondrial ribosomal genes, where not only were they useful for nematode molecular systematics, but they also possess sufficient sequence variation to discriminate between closely related nematode species [ 27 , 28 ]. The effectiveness of the 12S and 16S rRNA genes is further evidenced by applying the designed primers to amplify species across the four clades of parasitic nematodes.…”
Section: Introductionmentioning
confidence: 99%